Performance Evaluation of Propulsion Control Techniques for Autonomous Sailboat - dos Santos, Davi Henrique; Gonçalves, Luiz Marcos (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2020: Anais do XII Simpósio Brasileiro de Robótica e XVII Simpósio Latino Americano de Robótica, 2020)
Autonomous sailing is a relatively new field of research that has boomed over the recent years. There are several different strategies in literature for autonomous sailboat control, but yet no initiative to compare their performance that we know of. In this paper we propose a methodology for estimating the performance and comparing several propulsion control techniques for autonomous sailboats. Quantitative metrics are extracted from experiments in suitable scenarios to stress the control system. Three criteria are used for evaluation: time to target, energy consumption and safety, resulting in an initial performance estimate for the technique. We also propose an Improved Extremum Seeking technique that smooths the oscillatory behavior of classical Extremum Seeking. Some propulsion control techniques found in the state of the art were implemented in the open-source framework Ardupilot, and experiments in simulation allow for a first performance evaluation of the propulsion system.